2004
DOI: 10.1071/as04012
|View full text |Cite
|
Sign up to set email alerts
|

The Bias of Molecular Clump Identification Programs: the Example of the Carina Molecular Clouds

Abstract: A large scale 12 CO J = 1 → 0 molecular line map of the Carina molecular cloud complex was obtained with the Mopra radio telescope in order to investigate its spatial and kinematic structure. The data show a complex velocity structure in two distinct cloud regions -the Northern and Southern Carina clouds. Two different clump identification methods (gaussclumps and clumpfind) were applied to the data. Though both algorithms find a similar clump mass spectral index (1.95 and 1.8, respectively), the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 59 publications
(90 reference statements)
5
43
2
Order By: Relevance
“…The Rosette cloud has a similar total cloud mass than the CNC that is only slightly lower, and also harbors a large population of OB stars. However (as pointed out by Schneider & Brooks 2004;Schneider et al 1998), the Rosette Molecular Cloud is exposed to a much (about 10 times) weaker UV field than what we find in the Carina Nebula. This order-of-magnitude difference in the level of the radiative feedback may explain the differences in the cloud structure of these two complexes.…”
Section: Relative Importance Of Massive Star Feedback and Primordial contrasting
confidence: 44%
See 1 more Smart Citation
“…The Rosette cloud has a similar total cloud mass than the CNC that is only slightly lower, and also harbors a large population of OB stars. However (as pointed out by Schneider & Brooks 2004;Schneider et al 1998), the Rosette Molecular Cloud is exposed to a much (about 10 times) weaker UV field than what we find in the Carina Nebula. This order-of-magnitude difference in the level of the radiative feedback may explain the differences in the cloud structure of these two complexes.…”
Section: Relative Importance Of Massive Star Feedback and Primordial contrasting
confidence: 44%
“…For example, in the PDR in the Orion KL region, G 0 values up to 10 4 −10 5 have been determined (see references in Schneider & Brooks 2004). Such high local values are, however, only found in clouds located very close (less than 1 parsec) to individual high-mass stars, i.e., restricted to very small cloud surface areas.…”
Section: Strength Of the Radiative Feedbackmentioning
confidence: 99%
“…However, there is a long-lasting controversy about its validity in theory (e.g., Ballesteros-Paredes & Mac Low 2002) and observations (e.g., Schneider & Brooks 2004;Heyer et al 2009). Recently, a study of Lombardi et al (2010), using extinction maps of five molecular clouds, has concluded that all clouds in their sample have identical average column densities above a given extinction threshold.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain, for example, why many molecular line studies failed to detect a linewidth-size relation in molecular clumps (e.g. Loren 1989;Simon et al 2001;Schneider & Brooks 2004). In any case, it is difficult to transform model results into "observables" such as the 3D-or projected (on the plane of the sky) emission and velocity structure of an observed molecular line.…”
Section: Introductionmentioning
confidence: 99%